2002
DOI: 10.1128/jvi.76.8.3981-3995.2002
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Simian Immunodeficiency Virusnefin Immune Cells of Transgenic Mice Leads to a Severe AIDS-Like Disease

Abstract: In order to study the functions of simian immunodeficiency virus (SIV) Nef in vivo in a small-animal model, we constructed transgenic (Tg) mice expressing the SIV mac 239 nef gene in the natural target cells of the virus under the control of the human CD4 gene promoter (CD4C). These CD4C/SHIV-nef SIV Tg mice develop a severe AIDS-like disease, with manifestations including premature death, failure to thrive or weight loss, wasting, thymic atrophy, an especially low number of peripheral CD8؉ T cells as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 70 publications
2
21
0
Order By: Relevance
“…Studies from Jolicoeur's laboratory showed that transgenic mice expressing Nef under the control of the human CD4 gene promoter develop a severe AIDS-like disease, with manifestations including premature death, failure to thrive, thymic atrophy, and an especially low number of peripheral CD8ϩ T cells as well as a low number of peripheral CD4ϩ T cells. 28,29 These phenotypes are quite similar to those observed in homozygous Tg26 mice but not in heterozygous mice. The observed difference in phenotype could also be caused by the level of transgene expression in CD4ϩ cells, although it has never been examined.…”
Section: Discussionsupporting
confidence: 70%
“…Studies from Jolicoeur's laboratory showed that transgenic mice expressing Nef under the control of the human CD4 gene promoter develop a severe AIDS-like disease, with manifestations including premature death, failure to thrive, thymic atrophy, and an especially low number of peripheral CD8ϩ T cells as well as a low number of peripheral CD4ϩ T cells. 28,29 These phenotypes are quite similar to those observed in homozygous Tg26 mice but not in heterozygous mice. The observed difference in phenotype could also be caused by the level of transgene expression in CD4ϩ cells, although it has never been examined.…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, as shown in a transgenic mouse model, it is sufficient to express HIV-1 nef to trigger an AIDS-like disease (Hanna et al, 1998;Simard et al, 2002). The N-terminal region of Nef including the myristoylation site has been shown to be crucial for the development of an AIDSlike disease in mice (Hanna et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Only littermates were compared. All mice used for this work were kept under specificpathogen-free conditions as described previously (59), and all experiments were approved by the Institutional Animal Ethics Committee.…”
Section: Methodsmentioning
confidence: 99%